The PIK3CA H1047R Mutation Confers Resistance to BRAF and MEK Inhibitors in A375 Melanoma Cells through the Cross-Activation of MAPK and PI3K-Akt Pathways - Saverio Candido; Rossella Salemi; Sara Piccinin; Luca Falzone; Massimo Libra (MDPI AG, 2022)
The targeting of the Mitogen-Activated Protein Kinase (MAPK) signalling pathway in melanoma improves the prognosis of patients harbouring the V-Raf Murine Sarcoma Viral Oncogene Homolog B1 (BRAF) mutation. However, a fraction of these patients may experience tumour progression due to resistance to targeted therapy. Mutations affecting the Phosphoinositol-3-Kinase (PI3K)-Akt pathway may favour the onset of drug resistance, suggesting the existence of a crosstalk between the MAPK and PI3K-Akt pathways. We hypothesized that the inhibition of both pathways may be a therapeutic option in resistant melanoma. However, conflicting data have been generated in this context. In this study, three different A375 cell melanoma models either overexpressing or not expressing the wild-type or mutated form of the PhosphatidylInositol-4,5-bisphosphate 3-Kinase Catalytic Subunit Alpha (PIK3CA) gene were used to clarify the therapeutic response of melanoma to BRAF, Mitogen-Activated Protein Kinase Kinase 1 (MEK), and PI3K inhibitors in the presence of the PIK3CA H1047R mutation. Our data strongly support the notion that the crosstalk between the MAPK and PI3K-Akt pathways is one of the main mechanisms associated with melanoma development and progression and that the combination of MAPK and PI3K inhibitors may sensitize melanoma cells to therapy.